The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1055/s-0030-1254170
|View full text |Cite
|
Sign up to set email alerts
|

Mundgesundheit erwachsener Athleten mit geistiger Behinderung

Abstract: In 2008 the summer games of Special Olympics Germany took place in Karlsruhe, Germany. The athletes were offered on site the opportunity to have a voluntary and free dental examination. The examinations were performed by dental clinicians in rooms which were equipped with dental chairs. Data were collected following the criteria of WHO. 420 adult athletes took part in the dental examination. Their age ranged between 18 and 70 years and their mean age was 30.8 years. Nearly two thirds of the participants were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
2
0
8
Order By: Relevance
“…Im Vergleich zu den bei Angehörigen lebenden Teilnehmern nehmen die aus Wohnheimen öfter am Check-up, an der Hautkrebsvorsorge, der Gebärmutterhals-und Tastuntersuchung der Brust teil, doch seltener an der Gesundheitsförderung. [15,7] vor 1-2 Jahren 16 [15] 9,4 [8,7] vor 2-5 Jahren 11 [5] 6,5 [2,9] vor mehr als 5 Jahren 9 [30] 5,3 [17,4] weiß ich nicht 5 [ Mit 97 % geben fast alle einen festen Hausarzt an, den sie zuerst bei Gesundheitsproblemen aufsuchen. Darüber hinaus werden insbesondere Nerven-, HNO-, Haut-, Augenärzte und Orthopäden deutlich häufiger in Anspruch genommen.…”
Section: Discussionunclassified
“…Im Vergleich zu den bei Angehörigen lebenden Teilnehmern nehmen die aus Wohnheimen öfter am Check-up, an der Hautkrebsvorsorge, der Gebärmutterhals-und Tastuntersuchung der Brust teil, doch seltener an der Gesundheitsförderung. [15,7] vor 1-2 Jahren 16 [15] 9,4 [8,7] vor 2-5 Jahren 11 [5] 6,5 [2,9] vor mehr als 5 Jahren 9 [30] 5,3 [17,4] weiß ich nicht 5 [ Mit 97 % geben fast alle einen festen Hausarzt an, den sie zuerst bei Gesundheitsproblemen aufsuchen. Darüber hinaus werden insbesondere Nerven-, HNO-, Haut-, Augenärzte und Orthopäden deutlich häufiger in Anspruch genommen.…”
Section: Discussionunclassified
“…Compared with representative data on the oral health of German adults, individuals with intellectual disabilities had more extracted teeth than normal adults,[42] and the same was reported among German athletes with ID. [43] In other countries, it was also observed that, due to the reduced cooperation, the dental treatment for persons with intellectual disabilities consisted mostly of extractions. [644] This phenomenon may be the result of the tendency for emergency extractions (because of delayed seeking of treatment) or due to difficulties in behavioral management during dental procedures favoring measures that are less technique sensitive such as the extraction of teeth rather than their restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Studien wurden zwischen 2007 und 2018 in Baden-Württemberg, Sachsen und Nordrhein-Westfalen [ 15 – 17 ] durchgeführt. Eine weitere Studie wurde 2008 bei Athleten mit geistiger Behinderung im Rahmen einer nationalen Sportveranstaltung von Special Olympics Deutschland durchgeführt [ 18 ]. In Tab.…”
Section: Ergebnisseunclassified
“…Die vorliegende Literaturübersicht zeigt, dass in Deutschland Studien zur Prävalenz von Karies bei Menschen mit Behinderung nur in sehr geringer Zahl und fast nur in umschriebenen Regionen von 4 Bundesländern durchgeführt wurden. Lediglich in den Studien, die bei Athleten mit geistiger Behinderung im Rahmen von nationalen Sommerspielen von Special Olympics Deutschland durchgeführt wurden, stammten die untersuchten Personen aus allen Teilen Deutschlands [ 7 , 18 ]. Es fällt außerdem auf, dass nur in 2 Studien die Kariesprävalenz sowohl von Kindern und Jugendlichen mit Behinderung als auch von solchen der Allgemeinbevölkerung in derselben Region bestimmt wurde [ 8 , 12 ].…”
Section: Diskussionunclassified